The Role of Nurse Leaders in the Well-being of Clinicians. (July 2021) - Pappas, Sharon
Abstract : This column reviews the concept of humanism in leadership. After surviving a year perceived by many healthcare professionals as the most challenging of a generation, the author reflects on leadership essentials for rebuilding our nursing workforce.